Bacteriuria in Children with Special Reference to Structural Abnormalities of Urinary Tract - Qader, Md Abdul; Hasan, Md Jahidul; Hasan, Zahidul (Journal of Pediatric Nephrology, 2020)
Background and Aim: Urinary tract infection (UTI) can lead to adverse renal outcomes in the form of renal scarring and its consequences in children. Underlying congenital abnormalities of the kidney and urinary tract (CAKUT) play a crucial role in UTI recurrence and its outcome. Methods: This study was conducted to evaluate children aged 1 month to 18 years with bacteriuria retrospectively to assess recent trends of antimicrobial resistance, underlying structural abnormalities of the urinary tract, and severity of symptoms associated with it. Ultrasonography was done in children under 2 years with a history of recurrent UTI to exclude associated structural abnormalities of the urinary tract. Results: Of 255 studied children, 58% were female. Ultrasonography of the kidney and bladder was performed in 116 children, which revealed CAKUT in 38% (n=44). Children with CAKUT commonly presented with fever (36%) alone or in combination with other features. The most common pathogen was E coli (60%), which was very sensitive to intravenous aminoglycosides (95-100%) and carbapenems (96%) but had less sensitive to cephalosporins (43%). E coli showed higher resistance to oral cephalosporins and quinolones (62% and 54%, respectively). E coli had a high (93%) and Klebsiella spp had a low (63%) sensitivity to nitrofurantoin. Conclusion: This study revealed that about one fifth of the children with bacteriuria had CAKUT. A higher resistance pattern was observed to commonly used oral antimicrobial agents, which eventually narrows down the choice of empirical antibiotic. Keywords: Child; Bacteriuria; Urinary Tract Infection; Urinary Tract Abnormalities.